Case Report: Delayed Alemtuzumab-Induced Concurrent Neutropenia and Thrombocytopenia in Relapsing-Remitting Multiple Sclerosis. (February 2023) - Ganju, Akaansha; Stock, James C.; Jordan, Kim
Alemtuzumab is an anti-CD52 monoclonal antibody used to treat relapsing-remitting multiple sclerosis following failure of second-line medications. It is administered intravenously in 2 treatment sequences 1 year apart. This drug is frequently associated with mild infusion reactions within days of administration, increased infection risk, and long term adverse events from secondary autoimmunity. Alemtuzumab-induced serious immune-mediated thrombocytopenia (ITP) is well-reported and occurred in 1.0-2.2% of participants in initial phase 2 and 3 trials for multiple sclerosis. Significant neutropenia, however, is rare and was only observed in 0.1% of study participants. Delayed neutropenia and/or ITP is thought to occur from secondary autoimmunity. Few case reports have described severe neutropenia occurring beyond 2 months of last alemtuzumab dose. We present an unusual case of delayed combined neutropenia and thrombocytopenia that occurred 15 months after the second infusion of alemtuzumab. The patient was asymptomatic and presented following discovery of neutropenia and thrombocytopenia during routine laboratory studies. The patient responded to steroids initially and was discharged, although outpatient cell counts subsequently revealed recurrent neutropenia and ITP. The adverse drug reaction probability (Naranjo) scale was completed and showed probable likelihood that the adverse event was alemtuzumab-related. Long term screening for delayed hematologic abnormalities, at least 4 years after initial dose, is necessary when using alemtuzumab. Greater research is needed to understand the mechanism of drug-associated neutropenia.